2009
DOI: 10.1007/s00213-009-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor/nitrergic system blockage augments antidepressant-like effects of paroxetine in the mouse forced swimming test

Abstract: We suggested, for the first time, a possible role for NMDAR/NO signaling in the antidepressant-like effects of paroxetine, providing a new approach for the treatment of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 75 publications
(77 reference statements)
5
13
0
Order By: Relevance
“…We showed that anti-depressant like effect of lamotrigine was boosted by using different types of NMDA receptor antagonists, supporting the implication of NMDA in antidepressant-like effect of lamotrigine. Our data are in consistent with other studies, demonstrating the antidepressant-like effect of NMDA receptor antagonists in FST [28,30,68].…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…We showed that anti-depressant like effect of lamotrigine was boosted by using different types of NMDA receptor antagonists, supporting the implication of NMDA in antidepressant-like effect of lamotrigine. Our data are in consistent with other studies, demonstrating the antidepressant-like effect of NMDA receptor antagonists in FST [28,30,68].…”
Section: Discussionsupporting
confidence: 96%
“…L-NAME and 7-NI were administered 45 and 30 min prior to FST, respectively, in lamotrigine or saline-treated groups. Also, sub-effective dose of L-arginine (750 mg/kg) [28] was injected 30 min before the effective dose of lamotrigine (10 mg/ kg). The corresponding control groups only were given normal saline.…”
Section: Treatmentsmentioning
confidence: 99%
“…Our results are in accordance with studies that have shown that NOS inhibitors (Wegener et al, 2003) and reduction of NO levels within the hippocampus can induce antidepressantlike effects, thus implicating endogenous hippocampal NO in the neurobiology of depression (Joca and Guimarães, 2006). Similarly to our results, the antidepressant-like effects of escitalopram, paroxetine, and venlafaxine were also blocked by pretreatment with l-arginine (Dhir and Kulkarni, 2007;Ghasemi et al, 2009;Zomkowski et al, 2010). These results indicate that the effect of AE in the TST may be dependent on, at least in part, the inhibition of NO synthesis.…”
Section: Discussionsupporting
confidence: 96%
“…showed dose-dependent reduction in immobility time (Fig. 4), as reported previously (Lucki et al, 2001;Ghasemi et al, 2009). Neither olanzapine nor risperidone showed any effects in the forced-swim test at the doses used.…”
Section: Tablesupporting
confidence: 87%